The use of lectures: effective pedagogy or seeds scattered on the wind? - Loughlin, Colin; Lindberg-Sand, Åsa (Higher education, 2023)
This case study of large-class teaching at a UK university focuses on the place of large-scale lectures in academics’ approaches to teaching, their use by students in their studies, and their relationship to institutional quality assurance policies. The case is a second-year module comprised of 180 students, and it includes two-hour lectures as the primary mode of teaching. The data is drawn from a range of sources including observations, interviews, focus groups, institutional documentation, and a student survey. Observations revealed largely transmissive lectures with little student interaction. The analytic framework of constructive alignment and outcome-based education is used to examine the promoted educational values and the practice experienced by students. The results are further explored in relation to two texts celebrating 50 years since publication: Donald Bligh’s What’s the Use of Lectures and Benson Snyder’s The Hidden Curriculum , Both highlight the dissonance of espoused approaches to teaching, and the realities of large-class environments. While the institutional literature foregrounds student-centred, ‘active learning’ approaches, the teacher-centred practice observed would have been very familiar to Bligh and Snyder; the principles of constructive alignment were visible only at the policy level. The implicit reward mechanisms of the hidden curriculum ensure that the majority of students succeed and are satisfied with the educational offering. The students who attended the lectures appeared to enjoy them and indicated that the primary benefits are the structure offered by live lectures and the support of the peer networks which develop as a result of attendance.